Obstacles to the development of palm tree cultivation and date production in Al-Muthanna Governorate (Texas Journal of Multidisciplinary Studies, 2022)
The cultivation of palm trees is one of the predominant agricultural activities, practiced by the peasants of Al-Muthanna Governorate since ancient times, it has social, environmental and economic importance, contribute to increasing the local production and the national product of the country, it was exposed to geographical obstacles (both natural and human), and other biological (insects and diseased pests), caused challenges and problems, it negatively affected the cultivation of palm trees and its production of dates, both in terms of quantity and quality, that is why these obstacles were studied in the years (2020 and 2021), in order to find appropriate solutions, in line with the stages of growth of the first palm trees to the stages of maturity and marketing, in addition to highlighting the benefits of all its waste, in order to benefit from them in the food, household and heritage industries that have been circulating for thousands of years. The study suggested providing technical and material support to workers in the cultivation of palm trees, providing good quality seedlings, and carry out periodic and continuous campaigns to combat pests and diseases that affect palm trees and their fruits.